An empirical study on the determinants of tax morale using structural equation model (SEM): A Philippine particularity - Pacaldo, Raymond S. (Animo Repository, 2018)
Tax morale can be determined through economic, political and demographic indicators. As such, this paper investigates the effect of tax enforcement and trust in government moderated by demographic characteristics on the tax morale of firms in the Philippines. Using the data taken from the database of Business Environment and Enterprise Performance Survey (BEEPS), 865 firms were analyzed through partial least squares on structural equation of modelling (PLS-SEM). The results show that trust in government has a positive relationship with tax morale unlike tax enforcement. Also, organizational form and location demonstrate a negative relationship to the firms tax morale. Thus, the study concludes that the tax morale of firms in the Philippines can be heavily determined by trust in government while sole proprietorship businesses as compared to corporations, and firms in Metro Manila in contrast to firms outside have low tax morales.